Kondisi Sosial Ekonomi Masyarakat Nelayan Pantai Lebih Kecamatan Gianyar - ARTANA, GEDE ADI; SUAMBA, I KETUT; DJELANTIK, A.A. AYU WULANDIRA SAWITRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2024)
Socio-Economic of the Fisherman Communities at Lebih Beach, Gianyar Distric, Gianyar Regency. The problems seen in the socio-economic conditions of our fishermen are very different from the potential of their natural resources. In reality, the condition of fishing communities is relatively lagging behind economically, socially and culturally compared to other community groups. The coastal area of Gianyar has problems such as severe abrasion that threatens fishermen, so some fishermen in Gianyar, especially Pantai Lebih fishermen, not only work as fishermen but also open businesses for side jobs. The purpose of this study is to analyze the socioeconomic conditions of the community and the obstacles faced by fishermen on the coast of More Gianyar Regency. This research method is located in Pantai Lebih with 67 respondents with 9 indicators contained in the variables of this study. Using data analysis i.e. qualitative descriptive analysis and revenue analysis. The results obtained where the social conditions of fishermen on More Beach refer to the productive age who have an averagefamily dependents of four people. The economic conditions of fishermen have differences in capital needs, assets, income and catches. The average income is IDR 2.184.328. Obstacles faced by coastal fishermen More from a social point of view, some fishermen are over 55 years old and it is difficult to find fishermen regeneration, economically the income is not large, so some fishermen increase their income by opening side businesses to meet their living needs such as opening restaurants and becoming private employees. The government should.